Application of bio-organic fertilizer, not biochar, in degraded red soil improves soil nutrients and plant growth - Zhaoxiang, Wu; Huihu, Li; Qiaoli, Liu; Changyan, Ye; Faxin, Yu (Rhizosphere, 2020)
Biochar (B) and fertilizer (organic fertilizer, OF and synthetic fertilizer, CF) are frequently applied to improve ecosystem function and increase crop productivity in degraded soil. Nonetheless, the effects and mechanism of biochar in combination with OF and CF on degraded red soil was unclear. The aim was to study the influence of biochar and fertilizer related amendments in a degraded red soil on the rhizosphere microbiome of Plantago lanceolate under controlled condition. Soil was amended with rice husk biochar (5%, w/w), bio-organic fertilizer (5%, w/w), biochar (5%, w/w) + bio-organic fertilizer (5%, w/w), synthetic fertilizer (0.5%, w/w) and biochar (5%, w/w) + synthetic fertilizer (0.5%, w/w), in a greenhouse experiment. Illumina high throughput sequencing and PICRUSt analysis of functional gene prediction were employed to characterize the rhizosphere microbial community and its functional component involved in nitrogen (N) cycling and soil carbon (C) degradation. At harvest of 90 days, plant growth was highest with bio-organic fertilizer amendment, followed by biochar + synthetic fertilizer. Compared to the control, bio-organic fertilizer related amendment increased microbial diversity indexes (Ace, Sobs and Chao), but synthetic fertilizer decreased them significantly. Principal co-ordinates analysis showed that the microbial community was separated by the type of fertilizer, but not biochar. Redundancy analysis (RDA) at the phylum level further showed that electrical conductivity and soil carbon affected bacterial community, whereas alkaline nitrogen had a significant effect on the fungal community. PICRUSt analysis exhibited that bio-organic fertilizer related amendments decreased the abundance of labile C (glucoamylase and beta-galactosidase) and increased recalcitrant C degrading genes (catalase and endoglucanase). Predicted N cycling genes abundance increased with the addition of bio-organic fertilizer (nifD, amoA·amoB, Hao, nrfA, nirK and nosZ) and biochar + bio-organic fertilizer (amoA·amoB, Hao, narG, nrfA, nirk and nosZ). Biochar did not alter the relative abundance of phylum-level taxa and predicted functional genes in the absence of fertilizer. Via regulation of soil microbial community, bio-organic fertilizer amendment had positive impacts on N cycling, however, enhanced recalcitrant C degrading and inhibited labile C degrading.